2005
DOI: 10.5034/inquiryjrnl_42.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Finances and Patient Safety Outcomes

Abstract: Hospitals recently have experienced greater financial pressures. Whether these financial pressures have led to more patient safety problems is unknown. Using the Healthcare Cost and Utilization Project (HCUP) State Inpatient Data for Florida from 1996 to 2000, this study examines whether financial pressure at hospitals is associated with increases in the rate of patient safety events (e.g., medical errors) for major surgeries. Findings show that patients have significantly higher odds of having adverse patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 22 publications
4
98
3
Order By: Relevance
“…There have been few prior studies of the relationship between hospital margins and quality of care. Both Encinosa and Bernard 4 and Bazzoli et al 5 studied the effect of hospital margin on patient safety, but they reached contrary results. Encinosa and Bernard examined hospitals in Florida and found an association between lower margin and more frequent patient safety events, while Bazzoli et al studied hospitals in eleven states and found no impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been few prior studies of the relationship between hospital margins and quality of care. Both Encinosa and Bernard 4 and Bazzoli et al 5 studied the effect of hospital margin on patient safety, but they reached contrary results. Encinosa and Bernard examined hospitals in Florida and found an association between lower margin and more frequent patient safety events, while Bazzoli et al studied hospitals in eleven states and found no impact.…”
Section: Discussionmentioning
confidence: 99%
“…We used hospital operating margin because it is the most commonly used measure of hospital financial performance, 4,5 but we repeated our analyses for total margin and present these results in the Appendix (available online). Consistent with prior literature, we defined operating margin as net revenues from patient care and other operations (such as pharmacy, meal service, and parking lot receipts) minus total operating expenses divided by net revenues from patient care and other operations.…”
Section: Data On Margin and Hospital Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] We hypothesized that hospitals with higher profitability would have more funds available to expand service offerings such as the provision of CRT-D. We tested this hypothesis using Medicare Cost Report data to construct a broad measure of each hospital's operating margin. However, the 3-year trailing profitability average was not predictive of CRT-D receipt in our models either independently or in the final multilevel model.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there could be different impacts due to the type of system, as well as the type of hospital employing that system. Lastly, we did not account for the relationship to patient safety and quality of care, which is the other, overarching aim for promoting CPOE use (Encinosa and Bernard 2005). Future work could investigate these limitations.…”
Section: Limitations and Future Workmentioning
confidence: 99%